WORDPLAY TRANSLATION IN AUDIOVISUAL MEDIA: A COMPARATIVE ANALYSIS OF ENGLISH-UZBEK DUBBING IN ZOOTOPIA - Shakhnoza Pulatova Abdusamad kizi (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract The translation of wordplay remains one of the most challenging aspects of audiovisual translation due to the complex interaction between linguistic, cultural, and semiotic elements. This study investigates the translation strategies employed in the Uzbek dubbing of the animated film Zootopia, focusing on the rendering of English wordplay into Uzbek. Audiovisual texts are characterized by multimodal communication in which verbal expressions are closely connected to visual and acoustic components. Consequently, translators often face semiotic constraints that limit the possibility of preserving the formal features of wordplay. Using Dirk Delabastita’s taxonomy of wordplay translation strategies as a theoretical framework, this study examines four examples extracted from the film and compares the source and target language versions. The findings reveal that the Uzbek dubbing predominantly employs the Pun-to-Non-Pun strategy, prioritizing pragmatic effectiveness and functional adequacy over formal linguistic equivalence. While phonetic and rhyming patterns present in the original English dialogue are frequently lost, translators compensate through descriptive adaptation, cultural localization, and visual anchoring. The study concludes that the linguistic differences between English and Uzbek, together with the multimodal constraints of audiovisual translation, necessitate a shift from formal reproduction toward communicative effectiveness and audience comprehension.